Screening for the identification of oral language difficulties in Brazilian preschoolers: A validation study - Puglisi, ML; Blasi, HF; Snowling, M (American Speech-Language-Hearing Association, 2020)
Purpose This study aimed to develop and validate a screening questionnaire for the early identification of language difficulties in Brazilian Portuguese–speaking preschool children.